Pengaruh Manajemen Isu Terhadap Pemulihan Citra dan Loyalitas Pelanggan pada Followers Instagram @Scarlett_Whitening (Studi pada Scarlett Pasca Isu Pro Israel) - Niswati, Khoirun; Dwi Adnjani, Made (UNIVERSITAS SERAMBI MEKKAH, 2025)
This study aims to analyze the effect of issue management on image restoration and customer loyalty on @scarlett_whitening Instagram followers after the pro-Israel issue. Using image restoration theory which emphasizes communication strategies to restore images affected by negative issues. This research method uses an explanatory quantitative approach with a survey method through distributing questionnaires to 100 respondents and purposive sampling technique. Hypothesis testing uses simple linear regression analysis through the IBM SPSS application to test statistical data. The results of this study indicate that all validity test questionnaire items are declared valid with an r_count value greater than r_table (0.195), and all items are declared reliable with an r_count greater than r_table (0.600). The Simple Linear Regression analysis test results show that there is a significant influence between Issue Management on Image Recovery (Y1) with a coefficient value of 0.513. The Issue Management variable (X) is proven to have an effect on Customer Loyalty (Y2) with a coefficient value of 0.562. This shows that Issue Management has a positive and significant impact on Image Recovery and Customer Loyalty.